Mitochondrial genome of Megaphragma amalphitanum (Hymenoptera: Trichogrammatidae). (1st November 2016) - Nedoluzhko, Artem V.; Sharko, Fedor S.; Boulygina, Eugenia S.; Tsygankova, Svetlana V.; Sokolov, Alexey S.; Mazur, Alexander M.; Polilov, Alexey A.; Prokhortchouk, Egor B.; Skryabin, Konstantin G.
Abstract: The mitochondrial genome of the parasitic wasp Megaphragma amalphitanum is published in this paper. The mitochondrial DNA (mtDNA) is 15 041 base pairs (bp) in length and contained 13 protein-coding genes, 2 rRNA genes and 22 tRNA genes. The overall base composition of the genome in descending order was 45.67% A, 8.71% C, 39.63% T and 5.99% G, with a significant AT bias of 85.30%.